Proceedings of the 29th Annual Conference on Computer Graphics and Interactive Techniques 2002
DOI: 10.1145/566570.566608
|View full text |Cite
|
Sign up to set email alerts
|

Motion capture assisted animation

Abstract: We discuss a method for creating animations that allows the animator to sketch an animation by setting a small number of keyframes on a fraction of the possible degrees of freedom. Motion capture data is then used to enhance the animation. Detail is added to degrees of freedom that were keyframed, a process we call texturing. Degrees of freedom that were not keyframed are synthesized. The method takes advantage of the fact that joint motions of an articulated figure are often correlated, so that given an incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Several researchers have observed that there is a lot of redundancy in human motion,1 which is caused by the fact that human joints act in a coordinated manner for any kind of motion 11. Various animation methods, covering a wide range of techniques from inverse kinematics to procedural animation, make use of this property.…”
Section: Related Workmentioning
confidence: 99%
“…Several researchers have observed that there is a lot of redundancy in human motion,1 which is caused by the fact that human joints act in a coordinated manner for any kind of motion 11. Various animation methods, covering a wide range of techniques from inverse kinematics to procedural animation, make use of this property.…”
Section: Related Workmentioning
confidence: 99%
“…Similar to multi-resolution representations of texture [10] and movie texture [2], Pullen and Bregler modeled cyclic motions by multiresolution signals. The term motion texture was originally used by Pullen and Bregler (and suggested by Perlin) as their project name [34]. Our motion texture model is completely different from theirs.…”
Section: Related Workmentioning
confidence: 99%
“…Arikan and Forsyth [8] created a hierarchy of graphs and employed a randomized search algorithm for the synthesis of a new motion subject to user-specified constraints. Pullen and Bregler [12] segmented motion data into small pieces and rearranged them to match user-specified keyframes. In 2003, Arikan and his colleagues [9] presented a new search approach based on dynamic programming that supports user-specified annotations of the motion.…”
Section: Introductionmentioning
confidence: 99%